2002
DOI: 10.1139/f02-128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food web structure on the growth and bioenergetics of lake trout (Salvelinus namaycush)

Abstract: In this study, we compared energy budgets of lake trout (Salvelinus namaycush) populations in contrasting food webs. Nonpiscivorous lake trout (NPLT) reached a much smaller size and grew at a much slower rate than piscivorous lake trout (PLT) populations. Food consumption rates were, on average, 2–3 times higher in NPLT when they were expressed on a wet weight basis. However, only a slight (less than 10%) difference in their energy intake was detected once consumption rates were corrected for differences in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 41 publications
3
124
1
Order By: Relevance
“…First, increased reliance on Mysis and zooplankton would be less energetically efficient than foraging on larger prey fish or benthic invertebrates because predatory fish are more active when forced to feed on numerous, smaller prey (22). This increased energetic cost of feeding on small prey has been illustrated by studies that found predatory fish in lakes without pelagic prey fish had increased muscle activity and greater activity rates than those same species in lakes containing pelagic prey fish (23)(24)(25) and by studies showing that more active fish generally grow more slowly (26).…”
Section: Discussionmentioning
confidence: 99%
“…First, increased reliance on Mysis and zooplankton would be less energetically efficient than foraging on larger prey fish or benthic invertebrates because predatory fish are more active when forced to feed on numerous, smaller prey (22). This increased energetic cost of feeding on small prey has been illustrated by studies that found predatory fish in lakes without pelagic prey fish had increased muscle activity and greater activity rates than those same species in lakes containing pelagic prey fish (23)(24)(25) and by studies showing that more active fish generally grow more slowly (26).…”
Section: Discussionmentioning
confidence: 99%
“…If such a species lives in a community where a broad range of prey sizes is available, the transition to larger prey occurs smoothly as the individual grows (Paloheimo & Dickie 1966;Kerr 1971;Kerr & Ryder 1977;Piazza et al 2002), equation (2.3) is likely to hold throughout life, and potential length growth rate remains constant. If the prey field is truncated such that the availability of prey of suitable size does not keep pace with increases in predator size, then the slope of the potential growth curve (c 1 Ϫ c 2 ) will decline (dotted line in figure 1) owing to the increases in foraging costs associated with capturing relatively smaller prey (Piazza et al 2002). This decline in growth can be approximated using a new growth curve: 4) where t 1 , the intercept on the time axis for the new curve, decreases from zero in parallel with both the difference (h 0 Ϫ h 1 ) and the age at which the transition from h 0 to h 1 occurs.…”
Section: Potential Somatic Growthmentioning
confidence: 99%
“…With growth, maximum and minimum prey sizes generally increase, though the rate of change of these relationships may be modulated by species and habitat (Scharf et al 2000, Keeley & Grant 2001. These ontogenetic shifts to larger prey items may be important because growth efficiency is higher and metabolic costs are lower when feeding on larger prey (Pazzia et al 2002), and fish prey are generally higher in caloric value (Davis et al 1998).…”
Section: Introductionmentioning
confidence: 99%